COVID-19, physical activity and mental well-being in adults living in Mrkazi Province: an online cross-sectional study - Abbas Saremi; Alireza Aghababa; Alireza Bahrami; Mohiedin Bahari (فصلنامه ابن سینا)
Background: Due to the epidemic of COVID-19, health authorities have enacted laws for social distance from people.. The aim of this study was to investigate the changes in the level of physical activity during social distance caused by COVID-19 in Mrkazi Province, and the impact of physical activity on mental welfare. Materials and methods: In this cross-sectional study, a total of 558 adult residents of Markazi Province (20-60 years old) participated in a snowball sampling strategy to answer an online questionnaire. Physical activity was assessed using a valid 5-item questionnaire. The short Warwick-Edinburgh Mental Well-being Scale used for measuring mental The relationship between physical activity and mental health was studied using Pearson correlation. Results: In the study sample, 58.42% were female and 41. 58% were male. 97% of participants indicated that they adhered to social distancing guidelines. Due to the COVID-19 epidemic, the total time of physical activity in January 2020 significantly decreased compared to that in March 2020 in community-dwelling adults in Mrkazi province (P=0.001). A significant positive correlation was observed between the level of physical activity and mood score in men and women (r=0.14, p=0.001). Conclusions: In the present study of adults in Markazi Province and at the time of social distancing due to COVID-19, those who were physically active had better mental health. These results suggest that even light physical activity during the COVID-19 epidemic may help reduce the negative mental health effects associated with social distancing and quarantine adherence.